2021
DOI: 10.1080/03007995.2021.1885362
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, controlled, multicenter clinical trial to evaluate the efficacy and safety of oral sitafloxacin versus moxifloxacin in adult patients with community-acquired pneumonia

Abstract: Objectives: To evaluate the efficacy and safety of oral sitafloxacin versus oral moxifloxacin in the treatment of Chinese adults with community-acquired pneumonia (CAP). Patients and methods: This is a multicenter, randomized, open-label, positive-controlled clinical trial (chinadrugtrials.org.cn identifier: CTR20130046). CAP patients received sitafloxacin tablets 100mg once daily (qd) or 100mg twice daily (bid) to compare with moxifloxacin tablets 400mg qd, for 7-10 days. The primary outcome was non-inferiori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“… 14 , 15 , 18 In terms of safety, sitafloxacin 200 mg daily is generally well tolerated, with the most common side effects being gastrointestinal problems and liver function disorders. 19 , 20 A randomized trial comparing sitafloxacin with moxifloxacin found that the two drugs had a similar incidence of adverse effects. 19 Additionally, sitafloxacin and moxifloxacin are less associated with tendon rupture, which is an adverse effect of the second-generation quinolones 21 ; however, data on the safety of sitafloxacin are limited owing to its low availability.…”
Section: Introductionmentioning
confidence: 99%
“… 14 , 15 , 18 In terms of safety, sitafloxacin 200 mg daily is generally well tolerated, with the most common side effects being gastrointestinal problems and liver function disorders. 19 , 20 A randomized trial comparing sitafloxacin with moxifloxacin found that the two drugs had a similar incidence of adverse effects. 19 Additionally, sitafloxacin and moxifloxacin are less associated with tendon rupture, which is an adverse effect of the second-generation quinolones 21 ; however, data on the safety of sitafloxacin are limited owing to its low availability.…”
Section: Introductionmentioning
confidence: 99%
“…The antibacterial activity of quinolones (e.g., moxifloxacin and levofloxacin) commonly used to treat M. abscessus infections is unsatisfactory ( Choi et al, 2012a ). Sitafloxacin, a new fluoroquinolone that is effective against a broad range of bacteria, has the advantages of oral administration and superior safety ( Wu et al, 2014 ; Amano et al, 2016 ; Nakajima et al, 2016 ; Miyazaki et al, 2019 ; Mori et al, 2020 ; Li et al, 2021a , b ). Importantly, sitafloxacin exhibits antibacterial activity against M. tuberculosis and M. avium both in vitro and in vivo ( Tomioka et al, 1999 ; Sato et al, 2003 ; Asakura et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…A phase I clinical trial investigating the pharmacokinetics and tolerance to sitafloxacin found that a serum concentration of 1 mg/L was safely attained and well tolerated by healthy male volunteers administered a single 100 mg dose orally ( Li et al, 2021b ). This serum concentration is similar to the MIC 50 of sitafloxacin for M. abscessus found in the current study, thus a safe and effective dose can be achieved for treating M. abscessus clinically.…”
Section: Discussionmentioning
confidence: 99%
“…For those harboring parC G248T (S83I) and gyrA mutations, the effectiveness was further reduced to 18.8% [ 19 ]. Both sitafloxacin and moxifloxacin are newer-generation quinolones that exhibit a comparable incidence of gastrointestinal side effects [ 22 , 23 ]. These agents are less frequently associated with tendon rupture than levofloxacin, a prevalent fluoroquinolone drug [ 24 ].…”
Section: Introductionmentioning
confidence: 99%